2005
DOI: 10.1002/cne.20471
|View full text |Cite
|
Sign up to set email alerts
|

RhoA, RhoB, RhoC, Rac1, Cdc42, and Tc10 mRNA levels in spinal cord, sensory ganglia, and corticospinal tract neurons and long‐lasting specific changes following spinal cord injury

Abstract: Inhibition of RhoA has been shown to enhance axonal regeneration following spinal cord injury. Here we mapped mRNA expression patterns of RhoA, B, and C, Rac1, Cdc42, and Tc10 in spinal cord, sensory ganglia, and sensorimotor cortex in uninjured rats, and following spinal cord injury or sham laminectomy. In the intact spinal cord, neurons displayed high levels of Rac1, Cdc42, and Tc10 mRNA hybridization signal. GFAP-immunoreactive astrocytes expressed primarily RhoB and Rac1, while oligodendrocyte-like cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 44 publications
4
54
0
2
Order By: Relevance
“…In most studies, Rho activation has been associated with an increased migratory activity of astrocytes (John et al, 2004) and other cell types (Raftopoulou and Hall, 2004;Hall, 2005), which is consistent with our results. Moreover, Erschbamer et al (2005) reported that GFAPimmunoreactive reactive astrocytes showed a marked increase of RhoA expression after spinal cord injuries, supporting the promigratory activity of Rho in reactive astrocytes. In contrast, the inhibition of Rho activities promoted astrocyte migration in a few reports (Höltje et al, 2005;Borán and García, 2007), in which the role of Rho in astrocytes may contrast with Rho-dependent mechanisms in other cell types.…”
Section: Discussionmentioning
confidence: 82%
“…In most studies, Rho activation has been associated with an increased migratory activity of astrocytes (John et al, 2004) and other cell types (Raftopoulou and Hall, 2004;Hall, 2005), which is consistent with our results. Moreover, Erschbamer et al (2005) reported that GFAPimmunoreactive reactive astrocytes showed a marked increase of RhoA expression after spinal cord injuries, supporting the promigratory activity of Rho in reactive astrocytes. In contrast, the inhibition of Rho activities promoted astrocyte migration in a few reports (Höltje et al, 2005;Borán and García, 2007), in which the role of Rho in astrocytes may contrast with Rho-dependent mechanisms in other cell types.…”
Section: Discussionmentioning
confidence: 82%
“…These GTPases have been implicated in the progression of tumors from a broad range of cellular origins, and analyses at both the RNA and protein level have correlated their increased expression with tumor progression. Several Rho GTPases have been shown to regulate diverse signal transduction pathways and are involved in a variety of biological processes, including cell morphology, motility, proliferation, and apoptosis [11][12][13] . It has been known that gastric carcinogenesis is a multistep process with morphological progression involving multiple genetic and epigenetic events.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of CNS myelination, pathways known to influence oligodendrocyte development such as those initiated by the activation of integrin receptors (Liang et al, 2004) or the transmembrane protein Lingo-1 (Mi et al, 2005) can modulate the activities of cdc42, rac1, and rhoA. These GTPases are expressed by oligodendrocytes (Erschbamer et al, 2005), and, in primary oligodendrocyte cultures, their expression and activity are developmentally regulated (Liang et al, 2004). Although rhoA is expressed and active during early progenitor stages, the expression and activity of cdc42 and rac1 increase as differentiation proceeds (Liang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%